Blood donor eligibility criteria for medical conditions: A BEST collaborative study. Issue 7 (11th April 2022) - Jacquot, Cyril; Tiberghien, Pierre; van den Hurk, Katja; Ziman, Alyssa; Shaz, Beth; Apelseth, Torunn Oveland; Goldman, Mindy; ,
Abstract: Background and Objectives: Donor eligibility questions and criteria for medical conditions vary between blood centres, suggesting that they are based more on local regulations or experience, rather than on published data, which are limited. As the donor population ages, medical conditions become more common. We assessed donor health assessment criteria at blood centre members of the Biomedical Excellence for Safer Transfusion (BEST) Collaborative. Our aim was to compare eligibility criteria and determine their underlying basis. Materials and Methods: A REDCap survey was sent to blood centre participants, based on medical conditions of greatest interest suggested by the Donor Studies Team of the BEST Collaborative. Participants were asked about current donor health assessment questions, deferral criteria and the basis for their deferral policy (donor risk, recipient risk or both) for 20 medical conditions. Results: Complete responses were received from 26 blood donor centres (24 separate responses) representing a combination of hospital‐based centres, large regional centres and community/national blood centres in 14 different countries. Most centres specifically ask about heart and lung conditions, whereas fewer than half inquire about kidney, gastrointestinal or neurological conditions. North American blood centres tended to be less restrictive, while regulatory restrictions are more prevalent in Europe. Most participants felt that the criteria were based on regulatory requirements or experience, rather than on published data. Conclusion: There is considerable variability in criteria by region. Ideally, criteria would be more evidence‐based rather than based on regulatory requirements or experience. Deferral criteria must balance donor and recipient safety and maintain an adequate blood supply.